KEANEKARAGAMAN SEMUT (FORMICIDAE) DI SEKITAR DANAU ASAM SUOH LAMPUNG BARAT SEBAGAI SUMBER BELAJAR ENSIKLOPEDIA - Afiqah Khairunisa; Handoko Santoso; Rasuane Noor (EDUBIOLOCK, 2023)
This study aimed to (1) determine the genus of ants (Formicidae) around Asam Suoh Lake, West Lampung. (2) Know the index of ant diversity (formicidae) found around Asam Suoh Lake, West Lampung. (3) Know the benefits of research results in the form of encyclopedia learning resources. The research was conducted with a qualitative approach, the research was descriptive. The sampling technique was purposive sampling technique. Sampling of ants was done by baiting (bait trap), direct capture (hand collecting), and pitfall traps. The results of research that had been carried out around Asam Suoh Lake, West Lampung found 9 genus with 10 species, the species found were Tapinoma, Pheidole, Oecophylla, Solenopsis, Anoplolepis, Paratrechina, Dinomyrmex, Pachycondyla, Camponatus, and there were 2 species of genus, namely bau ants (Tapinoma sessile) and pudak ants (Topinoma melanocephalum). The results of the research that had been carried out were used in learning resources in the form of encyclopedias, learning resources in the form of encyclopedias got validation from design validators and materials got an average score of 84% and 100%, which means that the quality criteria for encyclopedias were very valid to use.